Entering the spotlight: Chitosan oligosaccharides as novel activators of CaCCs/TMEM16A. (August 2019) - Guo, Shuai; Wang, Hui; Pang, Chunli; Ren, Xuan; Li, Junwei; Wang, Xuzhao; Shi, Sai; Qi, Jinlong; Zhang, Hailin; Zhan, Yong; Chen, Yafei; An, Hailong
Graphical abstract: Abstract: Calcium-activated chloride channels (CaCCs)/TMEM16A control diverse fundamental physiological functions, and abnormal function of TMEM16A will lead to various diseases including asthma, hypertension, gastrointestinal hypomotility and cancers. Therefore, TMEM16A as drug targets for related diseases has been increasingly concerned by researchers. In this work, COS were reported as novel natural activators of TMEM16A. It was demonstrated that COS can activate TMEM16A in a concentration dependent manner, with an EC50 of 74.5 μg/mL. Then, fluorescence experiments and inside-out patch clamp experiments were combined to confirm that COS can directly activate TMEM16A. Further, we compared the activation effects of COS monomers DP2 to DP6, with DP3 the best activator. Molecular simulation was performed to find that the binding sites between DP3 and TMEM16A are E143 and E146 in TMEM16A, and it was speculated that COS and TMEM16A may be combined by electrostatic interaction. Finally, we verified that guinea pig ileum contraction was promoted by COS and the monomers through activating TMEM16A. Collectively, COS are novel efficient natural activators of TMEM16A, with potential to be developed to treatment diseases caused by down-regulation of TMEM16A including gastrointestinal hypomotility.